Ответ:
-5; -4; 1.
Пошаговое объяснение:
х (х² + 8х + 16) = 5(х+4)
х(х + 4)² - 5(х + 4) = 0
(х + 4)(х(х+4) - 5) = 0
(х + 4)(х² + 4х - 5) = 0
х + 4 = 0 или х² + 4х - 5 = 0
1) х + 4 = 0
х = - 4.
2) х² + 4х - 5 = 0
D = 16+20 = 36
x1 = (-4+6)/2 = 1
x2 = (-4-6)/2 = -5.
Ответ: -5; -4; 1.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
-5; -4; 1.
Пошаговое объяснение:
х (х² + 8х + 16) = 5(х+4)
х(х + 4)² - 5(х + 4) = 0
(х + 4)(х(х+4) - 5) = 0
(х + 4)(х² + 4х - 5) = 0
х + 4 = 0 или х² + 4х - 5 = 0
1) х + 4 = 0
х = - 4.
2) х² + 4х - 5 = 0
D = 16+20 = 36
x1 = (-4+6)/2 = 1
x2 = (-4-6)/2 = -5.
Ответ: -5; -4; 1.